Open Online Courses for Strengthening Laboratory-Based Detection of Antimicrobial Resistance in Pakistan - Saeed, Noureen; Zeeshan, Mohammad; Farooqi, Joveria; Shakoor, Sadia; Jabeen, Kausar; Malik, Faisal Riaz; Rao, Jason; Hasan, Rumina (Frontiers in Public Health, 2022)
Introduction: A good quality antimicrobial susceptibility testing (AST) dependend upon knowledge and skills of the laboratory staff. In Pakistan, the basic technical knowledge and skill of laboratory staff who performs AST is not optimal. Therefore, the objective of this study is to improve knowledge of laboratory staff involved in detection and reporting of antimicrobial resistance (AMR) through online open-access courses Methodology: On-line modules (n=7) consisting of 22 courses aimed at strengthening laboratory detection of AMR were developed. Courses were uploaded onto website www.parn.org.pk. Participants had the option of selecting courses of interest. On-line registration and pre-test were essential for course enrolment but post-test was optional. Number of registered participants and proportion that completed each course were computed. Paired t-test was used to assess the increase in mean scores. Association between participants working in public versus private laboratories and course completion rates were determined using chi-square tests Results: There were 227 participants from Pakistan (March 2018-June 2020). Largest number of registered participants and highest completion rate was noted for the antimicrobial susceptibility testing (AST) and biosafety courses, while quality related courses attracted lower interest. Comparison of pre and post-test performance using paired mean score for the individual courses showed statistically significant (p-value < 0.05) improvement in 13/20 courses assessed. Higher course completion rate was observed in participants from public versus private sector laboratories (56.8% vs 30.8%, p-value= 0.005). Conclusions: Our study suggests promising potential for OOCs towards addressing knowledge gaps in laboratory practice in resource limited settings. Key words: Open on-line Course, OOCs, antimicrobial resistance, antimicrobial sensitivity testing, laboratory strengthening, laboratory practice, Pakistan, Resource limited settings